THE EFFECT OF THE SFAE LEARNING MODEL ASSISTED BY VISUAL MEDIA ON STUDENTS’ SCIENCE LEARNING OUTCOMES AT SDN 232 PALEMBANG: PENGARUH MODEL PEMBELAJARAN SFAE BERBANTUAN MEDIA VISUAL TERHADAP HASIL BELAJAR IPAS SISWA SDN 232 PALEMBANG - Kadek Mulyani; Lukman Hakim; Budi Utomo; Nanang Winarno (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the effect of the Student Facilitator and Explaining (SFAE) learning model assisted by visual media on the science learning outcomes of students at SDN 232 Palembang. This is quasi-experimental study using a Nonequivalent Control Group Design. The sample consisted of 51 students, including 26 students of class IV.A as the experimental group and 25 students of class IV.B as the control group, selected using the Cluster Random Sampling technique. Data were collected through multiple-choice tests and analyzed using the Mann-Whitney-U test because the learning outcome data were not normally distributed. The results showed a Sig. (2-tailed) value of 0.011 <0.05, so Ho was rejected, and Ha was accepted. The average learning outcomes of the experimental group increased from 52.77 to 75.85, with an effect size of r = 0.354, indicating a medium effect. This indicates that the SFAE learning model, supported by visual media, has a significant moderate effect on students’ science learning outcomes at SDN 232 Palembang. These findings suggest that the SFAE model assisted by visual media, can be recommended as an alternative for active learning with conceptual science material in elementary schools.